Reduction of Blasting Induced Ground Vibrations Using High-Precision Digital Electronic Detonators - Lin, Fei; Liu, Rong; Zhang, Zhigang; Jiang, Deyi; Chen, Jinhua; Li, Yong (Frontiers in Earth Science, 2022)
This study aims to effectively control the effects of blast vibrations and improve the safety factor for personnel and facilities in blasting engineering. By employing high-precision digital electronic detonators according to the propagation and superposition principle of blasting vibration signals, a superposition prediction method based on single-hole blasting vibration waveform is proposed to determine the group-hole blasting vibration waveform. Experimental results show that the variation law of the predicted blasting vibration wave is consistent with that of the measured blasting vibration wave, and the error rate is less than 16%. Based on the proposed superposition prediction method, the variation law of particle vibration velocity peak with micro-differences in time is studied. Consequently, an optimal differential time interval (delay time) is obtained with regard to the blasting vibration reduction. The results are applied in a site leveling project, and the results show that the slight time difference between zones has an evident effect on vibration reduction. The maximum reduction achieved with the proposed method is superior (69.7%) to that obtained via other controlled blasting delay methods. This result has been successfully applied in a flat project in China.